Consumer Relations PT. First Media Tbk Terkait Layanan Internet Bermasalah di Perumahan Taman Janur Indah, Kelapa Gading - YUMNA NUR SHABRINA (Communications, 2019)
PT First Media Tbk is an Indonesian public company listed on the Indonesia Stock Exchange. First Media provides internet services, cable television, and data communications. By providing good service to customers, it can impact on the sustainability of the company. Such problems that occur at PT. First Media Tbk. Based on online news www.detik.com, number of customers of PT First Media Tbk complained about their internet services that are often problematic. Therefore, the formulation of the problem in this research is how consumer relations in private companies regarding customer complaints of PT. First Media Tbk related to internet service problem, in Taman Janur Indah Housing, Kelapa Gading? The author uses consumer relations variables. The variable has six dimensions, namely consumer and educational information, unfair and deceptive practices, handling consumer complaints, technology and complaints, marketing and complaints, and corporate liaison. This research uses quantitative research using descriptive method. The author collected the data using questionnaires, with interval scales. The population of this research is First Media customer at Taman Janur Indah Estate, Kelapa Gading, North Jakarta as many as 63 people and has 63 samples. Sampling technique in this research is using the census technique and the central tendency used is mean. The type of validity uses in this research is construction validity. Based on the results of the research of the overall dimension in this research the average citizen of Taman Janur Indah the customer of PT. First Media Tbk assesses the technology uses in responding to customer complaints is good enough, nevertheless the citizen of Taman Janur Indah First Media customers also assess that First Media internet service is often get troubled at the Taman Janur Indah housing complex in February 2017. The conclusion of this research is PT. First Media tbk has made a good connections to its customers through media technology such as establishing good relationships by responding and handling customer complaints through social media (facebook, twitter), e-mail, or through hotline services. The author recommends that First Media be able to provide fair and deceptive service in order to maintain the trust from customers and public towards the company.